Peran Guru PAI dalam Pembentukan Karakter Religius Siswa SMA Negeri 1 Selomerto Wonosobo - Aulia Fitri Musyafa; Sri Haryanto; Darul Munta (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
This study aims to determine the role of Islamic Religious Education (PAI) teachers in the formation of students' religious character at SMA Negeri 1 Selomerto Wonosobo and identify the supporting and inhibiting factors. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, interviews, and documentation of PAI teachers, students, and principals. The results of the study show that PAI teachers have an important role in shaping the religious character of students through various activities such as the habit of congregational prayers, reciting the Qur'an, reading Asmaul Husna, commemorating Islamic holidays (PHBI), and involvement in religious extracurricular activities. PAI teachers also play the role of teachers, guides, motivators, facilitators, and trainers in shaping students' religious attitudes. The supporting factors include a religious school environment, the support of the principal, collaboration between teachers, and the existence of structured religious programs. Meanwhile, the inhibiting factors found were the negative influence of social media, different family backgrounds of students, lack of student awareness, and limited time and resources. This study concludes that the success of the formation of students' religious character is greatly influenced by the active role of PAI teachers and the support of a conducive school environment.